Subcapsular hepatic hematoma. Serious complication during pregnancy - María Teresa Pérez Hernández; Viviana de la Caridad Sáez Cantero (Medisur)
Subcapsular hepatic hematoma is a rare complication during pregnancy, but potentially lethal and usually related to severe pre-eclampsia or HELLP syndrome (hemolysis, elevated liver enzymes and diminished platelets). Maternal and perinatal mortality in these cases is high, hence the importance of early diagnosis and timely and multidisciplinary treatment. This paper is a review on the subject, held in Ebsco, Hinari and Sci databases.